2022
DOI: 10.3390/plants11162177
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Vascular Occlusions and Crystal Deposits in the Xylem Sap Flow of Five Tunisian Grapevines

Abstract: Xylem vessels are essential pivotal organs in bulk hydraulic flow through the whole woody plant. However, environmental constraints generate disagreements in xylem structures, which are characterized by air emboli and occlusions formations, compromising water conductivity in grapevines. The aim of this work was to explore xylem morphology dynamics through the xylem sap flow of five Tunisian grapevine cultivars during the natural bleeding sap periods of 2019, 2021, and 2022. In fact, Sakasly, Khamri, Hencha, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…When the annular width changed from 2.0 to 2.6 μm, the Δp changed from 15.49 to 15.09 Pa, the q remained constant, and the ξ changed from 2.80×10 5 to 2.71×10 5 , which decreased by 3.21%. When the annular height changed from 2.0 to 2.6 μm, the Δp changed from 12.71 to 16.71 Pa, the q remained constant, and the ξ changed from 2.18×10 5 to 3.07×10 5 , which increased by 40.83%. When the annular spacing changed from 2.0 to 2.6 μm, the Δp changed from 15.47 to 15.10 Pa, the q remained constant, and the ξ changed from 2.79×10 5 to 2.71×10 5 , which decreased by 2.87%.…”
Section: The Vessel Structure Parameters On Flow Resistance Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…When the annular width changed from 2.0 to 2.6 μm, the Δp changed from 15.49 to 15.09 Pa, the q remained constant, and the ξ changed from 2.80×10 5 to 2.71×10 5 , which decreased by 3.21%. When the annular height changed from 2.0 to 2.6 μm, the Δp changed from 12.71 to 16.71 Pa, the q remained constant, and the ξ changed from 2.18×10 5 to 3.07×10 5 , which increased by 40.83%. When the annular spacing changed from 2.0 to 2.6 μm, the Δp changed from 15.47 to 15.10 Pa, the q remained constant, and the ξ changed from 2.79×10 5 to 2.71×10 5 , which decreased by 2.87%.…”
Section: The Vessel Structure Parameters On Flow Resistance Coefficientmentioning
confidence: 99%
“…It can be seen in Fig 11 that the ξ decreased with the increase of pitted inscribed circle diameter and pitted spacing, and increased with the increase of pitted width and pitted height. When the pitted inscribed circle diameter changed from 18 to 24 μm, the Δp changed from 7.92 to 4.62 Pa, the q changed from 8.40×10 −14 to 1.49×10 −13 m 3 /s, and the ξ changed from 1.69×10 5 to 0.18×10 5 , which decreased by 89.35%. When the pitted width changed from 2.0 to 5.0 μm, the Δp changed from 6.69 to 6.45 Pa, the q remained constant, and the ξ changed from 8.36×10 4 to 7.81×10 4 , which decreased by 6.58%.…”
Section: The Vessel Structure Parameters On Flow Resistance Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al investigated the transpiration and the water sources of T. ramosissima by using heat balance and oxygen isotopic analysis and found that daily sap flow was positively correlated with air temperature (Ta), photosynthetically active radiation (PAR), and the vapor pressure deficit (VPD) [28]. Bouamama-Gzara et al used the xylem sap flow of five Tunisian grapevine cultivars to investigate the xylem morphological dynamics, and the results showed that Hencha and Khamri were sensitive to environmental constraints, while the other three cultivars presented higher tolerance [29]. Ouyang et al investigated the impact of urbanization on sap flow of common evergreen tree species, and results show that the impact of pollutant discharge on average sap flux density was greater than that of climatic factors [30].…”
Section: Introductionmentioning
confidence: 99%